ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI SISWA DALAM PEMILIHAN PROGRAM KEAHLIAN DI SMK PGRI TANJUNG RAJA - wira azmi; harlin harlin; m. amri santosa (UNIVERSITAS SRIWIJAYA, 2015)
The objective of the research was to find out factors contributing students in choosing the vocational programs at SMK PGRI Tanjung Raja. The method of the research used was quantitative descriptive. The data was collected by using documentation, questionnaire, and skill test. The sample of the research was 45 students. The result of the research indicated that factors contributing students in choosing vocational programs at SMK PGRI Tanjung Raja came from internal and external factors. The internal factors included skills with sufficient criteria of assessment or contributed to the average percentage at 80.33%. It also included the skills with high criteria of assessment or contributed to the average percentage at 85.5%. The external factors included the result of entry score with sufficient criteria of assessment or contributed to the average percentage at 74.42%. Parents were also the external factors with high criteria of assessment or contributed to the average percentage at 87.47%. In other words, both internal and external factors had high criteria of assessment contributing students in choosing vocational programs in SMK PGRI Tanjung Raja which had average percentage at 81.93%.